A microwave irradiation-persulfate-formate system for achieving the detoxification and alkali-activated composite geopolymerization of the chromate-contaminated soil - Huang, Tao; Zhou, Lulu; Cao, Zhenxing; Zhang, Shuwen; Liu, Longfei (Ecotoxicology and environmental safety, 2021)
A microwave (MA) irradiation-persulfate-formate system was constructed to detoxify Cr contamination and solidify the geopolymerization of the alkali-activated composite material. Three series of experiments were correspondingly conducted to evaluate the treatment for the chromate-contaminated soil. The changes in the molar ratios of formate to persulfate and the mass rates of fortifier to soil led to a significantly greater reduction of CrVI in the detoxification experiments. The increase of blast furnace slag from 50% to 80% in the composite cementitious materials (CCM) intensified the immobilization efficiencies of chromate and the compressive strengths of geopolymer blocks. MA irradiation potentially enhanced the binding of Ca cations to the aluminosilicate compounds. The degree of reaction in the phenomenological kinetics model mathematically verified the geopolymerization process. Ettringite was formed within the structure of the geopolymer in the coupling system. Sulfate radicals released from persulfate not only contributed to the detoxification process but also strengthened the immobilization process. [Display omitted] •A microwave irradiation-persulfate-formate system was constructed to solve drawbacks.•Sulfate radicals contributed to detoxification and participated in solidification.•The catalytic production of CO2•− and the reduction of CrVI to CrIII were confirmed.•The formation of ettringite induced by sulfate radical enhanced geopolymerization.•The study expands the application of radicals and MA irradiation on the geopolymers.